(untitled) (FAVE Sección Ciencias Agrarias, 2025)
The use of swine deep-litter waste (CCP) in horticulture contributes to the circular economy. This study evaluated the effect of CCP on soil organic matter (MOS), microbial biomass carbon (CBM), enzyme activity (FDA), aggregate stability (EA<2mm), nitrate (NO3-), and phosphorus (P) content (0-20 cm), and on fresh weight (PF), dry weight (PS), dry matter (%MS), and use efficiency (UE) of CCP and N in lettuce (Lactuca sativa L.) in the field. Plots with (T1) and without (T0) CCP were compared during two cropping cycles per year, applying 6,3 kg m-2 and 2,1 kg m-2 of CCP in 2022 and 2023, respectively, in a DCA with 4 replicates and ANOVA analysis. CCP increased MOS by 25% without significantly affecting CBM or FDA. EA<2mm was higher in T1 (7,5%) compared to T0 (3,6%). CCP increased lettuce production (p<0,05) compared to T0, with differences of 2,17 kg m-2 for PF and 0,13 kg m-2 for PS, representing increases of 111% in PF and 72% in PS. A lower (p<0,05) %MS was observed in T1 (7,83%) compared to T0 (9,42%). The EU of the CCP and N was higher in the second year, demonstrating residual effects. An increase in soil NO₃⁻ and P content was detected, indicating potential environmental risks. CCP improves soil and crop parameters in the short term, but management strategies are needed to ensure long-term sustainability.